Razões e sensibilidade: um estudo sobre a construção do imaginário da docência feminina (1865 - 1917) - Xavier, Wilson José Félix (2015)
This research discusses the construction in the teaching of the feminization of social imagination in society of Paraiba, reflecting about the exemplary images in this process, i.e., how strong significance pictures established relationships between the idea of educating / teaching as something feminine and the expansion of female presence in the occupation of teaching positions at first in primary teaching. For such, a complex raid in discussions and analyzes of the images (verbal and visual) was necessary and the social imaginary. It consists of a study that used among other sources newspapers, magazines, pamphlet literature, scientific treatises, religious books, the iconography and the imaginary of the time, having as methodological reference the social imaginary perspective of Baczko (1985) and the notions of "symbolic handling" and "symbolic manipulation", inspired by the same author. This model of Sant'Anna Master, consecrated in Brazil since colonial times appears as important reference for the feminization of the act of educating and hence to the feminization of teaching. This image, extended in their symbolic attributes to his daughter Mary, in representing the Holy Mothers, helped to shape, along with the expansion of school education and purposeful action of political and intellectual elites, new modular images for women. At the beginning of the Republic, begins to leave the scene the image of "mother-teacher", inspired by the ethical and religious lines, to forge on its "ruins", images that point to the beginning of the formation of a "new" model republican and secular of "wife-mother-educator" as well as, new sensibilities and a new economy of affection for the teachers in schools.